The Construction of The Third Space in the Palestinian Diaspora’s Return Narratives in the Novel Maṣā’ir: A Postcolonial Narratological Study - Wahyu Mustika Rani; Muhamad Adji; Ikhwan Ikhwan (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
This article examines the complexities surrounding the return of the Palestinian diaspora to their homeland under Israeli occupation have been prominently explored in literary works, one of which is Rabai Al-Madhoun’s novel Maṣā'ir: Kūnshirtū al-Hūlūkawst wan-Nakbah (2015). This study aims to examine the construction of the “third space” as depicted in the novel, grounded in Homi K. Bhabha’s concepts of the unhomely and the third space. It seeks to uncover the textual strategies employed in constructing a space for the negotiation of identity within the novel. The literary text analysis employs Mieke Bal’s narratological framework across three layers text, story, and fabula integrated with Gérard Genette’s concept of metalepsis at the narrative level. The findings reveal that the dynamics of the diaspora’s return are presented in a fragmented and non-linear manner. Frequent shifts in narrators and focalizers blur the boundaries between narrative levels. Consequently, the “glorious” return idealized by the diaspora fails to serve as a means of restoring original identity. Instead, it triggers profound uncertainty, manifesting as a deep sense of estrangement or the unhomely. This experience of alienation in one’s own land becomes the catalyst that drives the characters to construct a third space within non-physical dimensions spiritual, imaginary, and psychological as well as through stories-within-stories. These are manifested in the characters’ thoughts, utterances, and writings, taking the form of metadiegetic narratives. This study concludes that the narrative of return in the novel is articulated through two narrative levels: the primary diegetic narrative and the metadiegetic narrative (fiction within fiction). Together, they construct a third space as a fluid, continuously articulated, and perpetually evolving identity.